2018
DOI: 10.5455/medscience.2017.06.8747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prevalence of musculoskeletal disorders in nurses: A systematic review

Abstract: Nurses exposure many risk factors in the hospital setting. Musculoskeletal disorders (MSDs) is a common health problem between work related disabilities and injuries in nurses. The aim of this review was to examine the prevalence of MSDs in nurses and also summarize risk factors, outcomes, solutions. An electronic search was conducted in Pub Med in January 2017. Publications in the last ten years were researched using the key words: "Work Related Musculoskeletal Disorders" and "Nurses". The initial electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 41 publications
(83 reference statements)
5
52
3
6
Order By: Relevance
“…Our results are in line with literature for other health-care professionals. According to a recent systematic review, nearly three out of four nurses employed in a hospital, suffered from pain or discomfort in at least one of any of musculoskeletal district during the past 12 months of work (5). In this review, the three musculoskeletal districts mostly affected where: lower back (65.3%), knees (56.2%) and neck (49.8%) (5).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results are in line with literature for other health-care professionals. According to a recent systematic review, nearly three out of four nurses employed in a hospital, suffered from pain or discomfort in at least one of any of musculoskeletal district during the past 12 months of work (5). In this review, the three musculoskeletal districts mostly affected where: lower back (65.3%), knees (56.2%) and neck (49.8%) (5).…”
Section: Discussionmentioning
confidence: 84%
“…According to a recent systematic review, nearly three out of four nurses employed in a hospital, suffered from pain or discomfort in at least one of any of musculoskeletal district during the past 12 months of work (5). In this review, the three musculoskeletal districts mostly affected where: lower back (65.3%), knees (56.2%) and neck (49.8%) (5). Also, results from a cross-sectional study conducted on nursing aides working in nursing homes showed that 87.4% of the study population experienced musculoskeletal disorders in the previous year (lower back 41.4%, shoulders 53%, knees 37.5%) [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22], which are exactly the same as our research results. Another systematic review of Soylar and Ozer in 2018 showed that the prevalence of MSDs varied between 33.0% and 88.0% and the most commonly affected body regions were lower back, shoulders, neck, knees, and wrists/hands [16]. Other recent studies in Asia, especially neighbouring countries in the same region, have shown similar results, such as in Malaysia (73.1%, most commonly affected sites were the neck and shoulders) [23], in China (79.5%, most commonly affected sites were the waist, neck, and shoulder) [24], in Lebanon (73.1%) [25], and a little higher in Thailand (83.9%, most commonly affected sites were lower back, shoulder, and knee) [26].…”
Section: Prevalence Of Ms In Various Anatomicalmentioning
confidence: 99%
“…In terms of careers, MSDs are the most frequent occupational health problem among health care workers, especially in nurses [15]. A recent systematic review of Soylar and Ozer found that the prevalence of MSDs varied between 33.0% and 88.0% and the work-related MSDs were associated with multiple factors such as demographic characteristics of nurses as well as physical, psychological, and organizational factors [16]. However, all studies were only considered and analyzed in relation to simple MSDs (in each anatomical site), but not to multiple MSDs or MMS.…”
Section: Introductionmentioning
confidence: 99%